1980
DOI: 10.3758/bf03204887
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic and semantic factors in the classification of nonspeech transient patterns

Abstract: Three experiments were conducted to investigate the role of both syntactic (i.e., temporal structure) and semantic (i.e.,knowledge of the source events) factors in a two-alternative (target/ nontarget) categorization task involving patterns of nonspeech acoustic transients. The results demonstrated that both factors can play an important role in the classification of such patterns. Although pattern syntax influenced performance in all three experiments, the effects of syntactic structure were clearest in Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 7 publications
(8 reference statements)
5
46
0
Order By: Relevance
“…The participants were much better at this task than would be expected chance, even though they were unable to report the rules underlying their decisions of well-formedness. This basic finding has been replicated by many authors (Brooks, 1978;Dulany, Carlson, & Dewey, 1984;Howard & Ballas, 1980;Mathews et al, 1989;Millward, 1981;Morgan & Newport, 1981).…”
mentioning
confidence: 64%
“…The participants were much better at this task than would be expected chance, even though they were unable to report the rules underlying their decisions of well-formedness. This basic finding has been replicated by many authors (Brooks, 1978;Dulany, Carlson, & Dewey, 1984;Howard & Ballas, 1980;Mathews et al, 1989;Millward, 1981;Morgan & Newport, 1981).…”
mentioning
confidence: 64%
“…There are a number of further studies which report facilitation of performance when participants are instructed speci®cally to look for the underlying rules but this only seems to occur when the rules are salient (e.g. Berry & Broadbent, 1988;Howard & Ballas, 1980;Reber et al, 1980). This phenomenon may account for the ®nding that participants displayed no learning in the observation condition of Experiment 1.…”
Section: Rule Searchmentioning
confidence: 98%
“…These studies have varied significantly in goals, and thus in both the research techniques employed and the answers found. Some studies have investigated the broad classification or grouping of large sets of diverse natural and artificial sounds (e.g., Ballas, 1993;Ballas & Mullins, 1991;Gygi, 2001;Howard & Ballas, 1980a, 1980b, 1981. More narrowly focused studies have investigated the identification of a specific source attribute for sounds produced in the laboratory under controlled conditions (e.g., Giordano & McAdams, 2006).…”
Section: Information Triangle and The Source-perception Loopmentioning
confidence: 99%